Hadith's source of reference finder browser extension / Mohamad Hafiz Khairuddin … [et al.] - Khairuddin, Mohamad Hafiz; Ahmad Saru, Nur Azalizana; Mohd Supir, Mohd Hafifi; Mishan, Mohd Taufik (2017)
Hadith is referred by Muslims after Al-Quran which contains words and acts of Prophet Muhammad (pbuh). Fast growth of internet and social media technology makes the Hadith not only can be found and read through from the internet but it is also can be shared and went viral as well. This creates an issue where people shared it on the internet does not make sufficient research on the authenticity of the hadith as well as its source of reference. This could lead to a possibility that people might mistakenly share a fabricated hadith over the internet. The dangers of sharing false hadith has been warned by the Prophet Muhammad (pbuh) in Sahih Al-Bukhari, Book No. 3, hadith no 109. Hadith's Source of Reference Finder Browser Extension is designed to help the internet user to check if the hadith that they found on the web has a valid source of reference. With this browser extension, even though it cannot replace any hadith experts to validate the authenticity of a particular hadith, it can promote a more cautious approach to the society when dealing with any hadith found on the internet. It is intended to encourage the internet users to at least, search whether a particular hadith found on the internet has a valid source of reference before they want to share or viral it over the internet. The designed browser extension uses Google Chrome browser as its platform. System Development Life Cycle is used as its development methodology to properly construct the browser extension. The browser extension prototype enables the internet user to check the reference source of the hadith by inserting a copied hadith text from the internet into the extension‘s text input box and the output will be displayed along with its similarity percentage of the original text. This paper discusses on how ICT technology can be used to encourage the public to take the initiative to check the source of reference pertaining to any Islamic material found in the internet.